A new digital measurement system for assessing the lip in patients with cleft lip and palate (CLP) - Andrea Grandoch; Marie Wegner; Teresa Kruse; Bert Braumann; Martin Dübbers; Florian Grill (Journal of Oral Biology and Craniofacial Research)
Objective: In order to better and more objectively assess and compare the aesthetics of the lip, we offer an inovative, digital measurement method. Patients and method: Patients were divided into 2 groups:a) patients with unilateral CLP andb) patients with bilateral CLP.Based on standardised photos from 3 different directions, lip symmetry and aesthetics were assessed. A new digital measurement system was used, which was integrated into a proven clinical programme. Different symmetry indices were compared with a non-cleft control group. In addition, the function was investigated and a standardised questionnaire was used. Results: In total, 92 patients with operated CLP could be recruitetd and showed significant residual asymmetry compared to the control group with 49 patients. The results were more symmetrical in group b) than in group a). In contrast, scar width and scar aesthetics as well as orofacial function were better in group a). The preoperative cleft width showed a positive correlation with the postoperative scar width and scar aesthetics. Socioeconomic factors were not related to surgical outcome. Satisfaction of affected children and parents correlated with objectively assessed scar aesthetics and function. There was no correlation between satisfaction and symmetry or cleft width or scar width. Conclusion: The presented measurement system can be used excellently and effectively in clinical routine, especially for the inexperienced examiner, for fast and yet detailed, objective recording of findings. The measurement results can be analyzed comparatively and interpreted predictively for diagnostics, planning and therapy.